2010
DOI: 10.1002/cbdv.201000005
|View full text |Cite
|
Sign up to set email alerts
|

Peptide Nucleic Acids (PNA) in Chemical Biology and Drug Discovery

Abstract: Introduction. -Since the introduction almost 20 years ago [1], peptide nucleic acids (PNAs) have caught the interest in many fields of science from pure chemistry, over (molecular) biology, drug discovery, and (genetic) diagnostics, to nanotechnology and prebiotic chemistry. Thus, a very wide variety of PNA derivatives and PNA-type molecules have been synthesized and characterized in terms of chemical properties and in terms of possible exploitation within nucleic acid recognition applications. Despite this we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
162
0
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 210 publications
(163 citation statements)
references
References 115 publications
0
162
0
1
Order By: Relevance
“…This opens the door for subnuclear targeting of epigenetic probes, including small molecules and modified proteinaceous material (17,18). Examples of synthetic targeting agents include pyrrole-imidazole polyamides and peptide nucleic acids (19,20). Despite the elegance of these strategies, however, their widespread application has been limited by the need for specialized chemical synthesis methods and by constraints associated with their genomic targeting (i.e., locus specificity) (19,21).…”
mentioning
confidence: 99%
“…This opens the door for subnuclear targeting of epigenetic probes, including small molecules and modified proteinaceous material (17,18). Examples of synthetic targeting agents include pyrrole-imidazole polyamides and peptide nucleic acids (19,20). Despite the elegance of these strategies, however, their widespread application has been limited by the need for specialized chemical synthesis methods and by constraints associated with their genomic targeting (i.e., locus specificity) (19,21).…”
mentioning
confidence: 99%
“…Gene-silencing oligomers decrease expression of reporter genes such as luciferase, activate endogenous genes such as b-galactosidase, and inhibit growth by targeting essential genes . Some of the attractive targets for antisense antibacterial therapy include essential genes such as acyl carrier protein (acpP) encoding the fatty acid biosynthesis protein Greenberg et al, 2010), bacterial RNA polymerases (Bai et al, 2011), fabIencoding enoyl-acyl carrier protein reductase and 16S rRNA (Nielsen, 2010). Prior studies have shown that PMO targeting the acpP gene was able to inhibit E. coli viability in vitro and in vivo in mice .…”
Section: Introductionmentioning
confidence: 99%
“…Over the past two decades, a growing number of PNA derivatives have been synthesized and successfully applied in molecular biology, diagnostics and therapeutics [4][5][6][7]. Recently, a novel non-classical PNA monomer, S-thyminyl-L-cysteine hydrochloride (compound 2), which consists of natural chiral cysteine and 5-hydroxymethyluracil [8], was reported by Yu and his co-workers [9,10].…”
Section: Introductionmentioning
confidence: 99%